Cartilage in therapy of renal cell cancer - Nurzyński, Paweł; Żołnierek, Jakub; Korniluk, Jan; Oborska, Sylwia; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2005)
Shark cartilage is big hope for patients with advanced cancer. An alleged lack of cancer in sharks constitutes a key justification for its use. Herein, both malignant and benign neoplasms of sharks and their relatives are described, including previously unreported cases from the Registry of Tumors in Lower Animals, and two sharks with two cancers each. Lack of controle of using nutritional supplements caused hipercalcemia. Neovastat (AE-941) is product of Aetarna Zentaris which tested in phase III trial in metastatic renal cell carcinoma patients refractory to immunotherapy. Comparison of the survival times between the AE-941 and placebo study drug groups did not show an overall difference (median 379 days versus 376 days, p = 0.505) in 305 metastatic renal cell carcinoma patients. More specifically, for the stratum Metastasis in one organ – ECOG 0, the median survival time was longer in the AE-941 group, compared with the placebo group, but not statistically significant (p = 0.068). Based on post-study exploratory analysis of a small subgroup of patients with only one metastatic site, ECOG = 0 and clear cell histology a survival benefit of AE-941 over placebo was observed. The following adverse events were reported more frequently in the A-941 group (by more than 5%) than in the placebo group: constipation (22.4% versus 16.1%, respectively) and arthralgia (19.1% versus 11.4%, respectively).